Preparation and Properties of Carboxymethyl Chitosan/Alginate/Tranexamic Acid Composite Films - Qing-Kun Zhong; Ze-Yin Wu; Ya-Qi Qin; Zhang Hu; Si-Dong Li; Zi-Ming Yang; Pu-Wang Li (Membranes, 2019)
In this study, the porous composite films of carboxymethyl chitosan/alginate/tranexamic acid were fabricated, with calcium chloride as the crosslinking agent and glycerin as a plasticizer. The composite films were characterized by scanning electron microscopy (SEM) and Fourier transform infrared (FTIR) spectroscopy. The properties of the composite films, including water absorption, air permeability, and cumulative release rate, were tested. In addition, their hemostatic performance was evaluated. The results showed that the appearance of the films with good adhesion was smooth and porous. FTIR showed that chemical crosslinking between carboxymethyl chitosan and sodium alginate was successful. The excellent cumulative release of tranexamic acid in the composite films (60–80%) gives the films a significant procoagulant effect. This has good prospects for the development of medical hemostasis materials.